'Conversion' from ulcerative colitis to Crohn's disease associated with corticosteroid treatment. Issue 8 (August 1994) - Dwarakanath, A D; Nash, J; Rhodes, J M
Abstract : A man who was a non-smoker presented with clinical, histological, and radiological features typical of distal ulcerative colitis. Prolonged treatment with corticosteroids was associated with the development of numerous granulomata, stricturing, and perianal disease. It is speculated that the immunosuppression associated with the corticosteroid treatment may have induced a change from ulcerative colitis to Crohn's disease of the colon. This case report lends support to the hypothesis that these conditions may just represent different forms of a continuum of inflammatory bowel disease.